The role of ferritin and carboxyhemoglobin as inflammatory biomarkers in sepsis and septic shock - Grigorescu Bianca-Liana; Coman Oana; Huțanu Adina; Fodor Raluca-Ștefania (Acta Marisiensis - Seria Medica)
Background: While increased carbon monoxide production in sepsis is well-documented, the role of carboxyhemoglobin blood level fluctuations as a potential indicator of disease progression in sepsis remains unclear.